MAGNETIC ANALYSIS OF ROTATING MAGNETIC FIELD DEVICES USED FOR STUDIES ON BLOOD CELLS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The study of the molecular-level effects in blood cells of the variable magnetic field requires the design of appropriate magnetic devices. In this article, four immobile configurations are analyzed: Helmholtz coils, Gramme coils, a 4-pole electromagnet, and a 6-pole electromagnet. These devices can create a rotating magnetic flux density, intense (up to hundreds of mT), of high frequency (up to 1 MHz) and with an appropriate degree of inhomogeneity (maximum 5 %) in the bioreactor area of 1 cm in diameter. The rotating field is created by supplying the component coils with currents having shifted phases. The original comparative numerical analysis with the help of COMSOL software highlighted the effect of the device geometry, the type of core and conductor, correlated with the working frequency, on the magnetic flux density level in the blood cells. Original and useful results were extracted from the analysis of the homogeneity of the magnetic field in the bioreactor domain.
Keywords: Electrical engineering computing; Magnetic analysis; Magnetic cores; Rotating magnetic field; Biological cells